Characteristics and dynamics of wind-driven upwelling in the Alaskan Beaufort Sea based on six years of mooring data. (April 2019) - Lin, Peigen; Pickart, Robert S.; Moore, G.W.K.; Spall, Michael A.; Hu, Jianyu
Abstract: Six years of mooring data from the Alaskan Beaufort Sea slope, together with meteorological observations and reanalysis fields, are used to quantify the occurrence of wind-driven upwelling and the associated atmospheric forcing. The canonical upwelling event, composited from 115 individual events, reveals that when the easterly wind is strongest the entire shelfbreak jet is reversed to the west. At the end of the event a bottom-intensified, eastward-flowing "rebound jet" spins up that is stronger than the normal shelfbreak jet. The cross-isobath flow has a three-layer structure with onshore flow in the surface layer, offshore flow in the middle of the water column, and onshore flow near the bottom. This is because the reversed shelfbreak jet is oriented slightly onshore which overwhelms the cross-isobath surface Ekman transport. The vertically-integrated along-isobath momentum balance supports this interpretation and indicates that the rebound jet is driven by the zonal gradient in sea surface height. During over two thirds of the events, Atlantic Water (AW) is upwelled to the shelfbreak, while for the remaining events only Pacific Water (PW) is upwelled. The primary driving factor behind this is the seasonal variation in the PW-AW interface depth offshore of the shelfbreak, which is controlled by the local wind stress curl. During summer, when PW-type events dominate, Ekman pumping associated with negative wind stress curl deepens the interface depth, limiting access to the Atlantic layer. Over the remainder of the year, when AW events dominate, Ekman suction associated with positive wind stress curl raises the interface. These variations are due to the influence of the two regional atmospheric centers of action — the Aleutian Low and the Beaufort High.